Mango marketing system in selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2008)
This study was carried out to identify the most efficient and suitable marketing channels of mango in some selected areas of Bangladesh by using primary data collected randomly from 90 farmers and 55 traders. Out of 55 traders, 15 were Bairals, 15 were Beparis. 9 Aratdar (local), 6 Aratdar (urban), 10 Retailers (both local and urban). According to the volume of mango handled and longevity or participation of the intermediaries in the channel, five major channels were identified as dominant in the study areas. The channel Farmer Bairal- Bepari-Aratdar (Dhaka)-Retailer (Dhaka)-Consumer ranked first. The results showed that channel V, Farmer-Retailer Consumer, possesses the highest marketing efficiency followed by channel IV, III, and II. The performance indicators revealed that the channel I and channel II were not relatively efficient in the mango producing regions. Unstable price of mango was the first rank problem in the study area. Establishment of mango processing plant in the intensive growing areas may be the remedy of the problem, which will ensure fair prices for the farmer. Key Words: Mango marketing, channels, problem. doi:10.3329/bjar.v33i3.1602 Bangladesh J. Agril. Res. 33(3) : 427-438, September 2008